Analysis of correlation between optical and microtomography measurements of cementation space in CAD-CAM ceramic crowns - Piras, Fernanda Furtado; Ferruzzi, Fernanda; Ferrairo, Brunna Mota; Ramalho, Ilana Santos [UNESP]; Bonfante, Estevam Augusto; Rubo, Jose Henrique (Elsevier B.V., 2020)
Statement of problem. Identical computer-aided design (CAD) parameters may be used to mill a variety of ceramic materials for computer-aided design and computer-aided manufacture (CADCAM) crowns. Whether milled crown spacing matches the designed parameters when more than a single evaluation method is applied is unknown. Purpose. The purpose of this in vitro study was to correlate the stereomicroscope and the microcomputer tomography (mu CT) 2-dimensional analysis of the cementation space with the replica technique in assessing 3 different ceramic materials. Materials and methods. The specimens were milled in lithium disilicate, resin nanoceramic, and zirconia (n=30). The cement space was measured at the marginal, axial, and occlusal regions. One hundred twenty measurements of each material were used to correlate the methodologies. Data were statistically evaluated with 2-way repeated measures ANOVA and the Tukey test (alpha=.05). The Pearson correlation coefficient was used for each region for both methodologies (mu CT and optical microscopy) separately. Results. For the mu CT analysis, no differences were observed (P>.05) among the materials, but the axial region showed a positive correlation with the marginal (r=0.957) and occlusal regions (r=0.349); the same was observed between the occlusal and marginal regions (r=0.338). However, for stereomicroscope evaluation, resin nanoceramic and zirconia present similar cementation space (P=960), both being different from lithium disilicate (P<.05). The marginal region presented a positive correlation with axial (r=0.149) and occlusal regions (r=0.344), but the axial region showed negative correlation with the occlusal surface (r=-0.205). Conclusions. The measurements of the scanned replicas were accurate when thinner sections were under measurement. Although the same space parameters were set in the CAD software program, definitive internal dimensions varied among the milled crowns.